Penjadwalan Waktu Istirahat Optimal Untuk Mengurangi Risiko Musculoskeletal Disorders Berdasarkan OCRA Index - Andriani, Debrina Puspita; Sugiono, Sugiono (Universitas Muhammadiyah Surakarta, 2016)
Repetitive tasks carried out by workers of packaging department of mineral water company led to some complaints of pain and fatigue on a particular body part of the workers, especially on their upper body part. This study aims to determine risk level of musculoskeletal disorders with OCRA index and provides optimal break schedule to reduce the risk level. Based on calculations using the OCRA index method, it is found that risk of injury to the workers were medium with high level of risk. Despite small workload of the operators, this may be caused by poor distribution of rest periods and lengthy working time for highly repetitive tasks. Improvement proposed in this study is type of work-compliant break time allocation. Optimal scheduling of which main objective is optimal break time is eventually obtained by applying enumeration algorithm with integer linear programming model. Based on OCRA index after improvement, it is clear that the proposal decreases the risk level of the workers.